Exploring the Usefulness of FinTech in the Dark Era of COVID-19 - PINSHI, Christian P. (Journal of Advanced Studies in Finance, 2021)
This article explores the potential opportunity of FinTech on the financial system in the dark and wicked era of COVID-19. We first provide a seven-figure overview of the unpleasant impact of COVID-19 on the financial system. FinTech sees itself on the one hand as a hope to rebalance the global financial system in this time of financial turmoil, and on the other hand becomes an ultimate weapon to strengthen the resilience of the financial system and respond to the crisis by ensuring the functioning system while respecting containment measures and preventing the spread of the virus.